Osteoblastoma with secondary aneurysmal bone cyst in the proximal femur of a 6-year-old boy: a rare case report - P., Umasankar; U., Lakshmi Priya; Zainudeen, Fadiya (International Journal of Contemporary Pediatrics, 2018)
Osteoblastoma is a rare bone forming neoplasm. It is extremely rare for osteoblastoma to present with secondary aneurysmal bone cyst. Authors present a case of a 6-year-old boy with osteoblastoma of the femur with secondary aneurysmal bone cyst. To the best of the knowledge, this is the first such case report of the lesion presenting in proximal femur.